Gd2O3 nanoparticles in hematopoietic cells for MRI contrast enhancement - Hedlund A (Dove Medical Press, 2011)
Anna Hedlund1,2, Maria Ahrén3, Håkan Gustafsson1,2, Natalia Abrikossova3, Marcel Warntjes2,4, Jan-Ingvar Jönsson5, Kajsa Uvdal3, Maria Engström1,21Division of Radiology, Department of Medical and Health Sciences, 2Center for Medical Image Science and Visualization, 3Division of Molecular Surface Physics and Nanoscience, Department of Physics, Chemistry, and Biology, 4Division of Clinical Physiology, Department of Medicine and Health Sciences, 5Department of Clinical and Experimental Medicine, Experimental Hematology Unit, Linköping University, Linköping, SwedenAbstract: As the utility of magnetic resonance imaging (MRI) broadens, the importance of having specific and efficient contrast agents increases and in recent time there has been a huge development in the fields of molecular imaging and intracellular markers. Previous studies have shown that gadolinium oxide (Gd2O3) nanoparticles generate higher relaxivity than currently available Gd chelates: In addition, the Gd2O3 nanoparticles have promising properties for MRI cell tracking. The aim of the present work was to study cell labeling with Gd2O3 nanoparticles in hematopoietic cells and to improve techniques for monitoring hematopoietic stem cell migration by MRI. Particle uptake was studied in two cell lines: the hematopoietic progenitor cell line Ba/F3 and the monocytic cell line THP-1. Cells were incubated with Gd2O3 nanoparticles and it was investigated whether the transfection agent protamine sulfate increased the particle uptake. Treated cells were examined by electron microscopy and MRI, and analyzed for particle content by inductively coupled plasma sector field mass spectrometry. Results showed that particles were intracellular, however, sparsely in Ba/F3. The relaxation times were shortened with increasing particle concentration. Relaxivities, r1 and r2 at 1.5 T and 21°C, for Gd2O3 nanoparticles in different cell samples were 3.6–5.3 s-1 mM-1 and 9.6–17.2 s-1 mM-1, respectively. Protamine sulfate treatment increased the uptake in both Ba/F3 cells and THP-1 cells. However, the increased uptake did not increase the relaxation rate for THP-1 as for Ba/F3, probably due to aggregation and/or saturation effects. Viability of treated cells was not significantly decreased and thus, it was concluded that the use of Gd2O3 nanoparticles is suitable for this type of cell labeling by means of detecting and monitoring hematopoietic cells. In conclusion, Gd2O3 nanoparticles are a promising material to achieve positive intracellular MRI contrast; however, further particle development needs to be performed.Keywords: gadolinium oxide, magnetic resonance imaging, contrast agent, cell labeling, Ba/F3 cells, THP-1 cells